Synthesis, electrochemical and spectroelectrochemical properties of thiazole-substituted phthalocyanines - KOCA, ATIF (ELSEVIER SCIENCE SA, 2015)
A new phthalonitrile derivative (3), bearing 2-(4-methyl-1,3-thiazol-5-yl) ethoxy- and chlorosubstituents at peripheral positions, was synthesized in this work. Cyclotetramerization of (3) in 1-hexanol gave the desired metallophthalocyanines (4-6). All of the synthesized compounds have been characterized by using elemental analysis, UV-vis, FT-IR, H-1 NMR and MS spectroscopic data. Aggregation behaviors of phthalocyanines were investigated in different solvents. Redox properties of the complexes were determined with voltammetric and in situ spectroelectrochemical measurements. Electrochemical and spectroelectrochemical measurements exhibit that the incorporation of the redox-active metal ions, Co-II and (MnOAc)-O-III, into the phthalocyanine core extends the redox richness of the Pc ring with the reversible metal-based reduction and oxidation couples in addition to the common Pc ring-based electron transfer processes. Assignments of the redox processes of the complexes were supported with in situ spectroelectrochemical measurements. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Thiazole; Aggregation; Electrochemistry; Spectroelectrochemistry; MICROWAVE-ASSISTED SYNTHESIS; MANGANESE PHTHALOCYANINE; METAL-FREE; PHOTODYNAMIC THERAPY; COBALT; COMPLEXES; METALLOPHTHALOCYANINES; IRON; RED; PHOTOSENSITIZERS